2000
DOI: 10.1073/pnas.050282397
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine 2B receptor regulates cell-cycle progression: Cross-talk with tyrosine kinase pathways

Abstract: In this paper, we present evidence that activation of 5-hydroxytryptamine 2B (5-HT2B) receptors by serotonin (5-HT) leads to cell-cycle progression through retinoblastoma protein hyperphosphorylation and through activation of both cyclin D1͞cdk4 and cyclin E͞cdk2 kinases by a mechanism that depends on induction of cyclin D1 and cyclin E protein levels. The induction of cyclin D1 expression, but not that of cyclin E, is under mitogen-activated protein kinase (MAPK) control, indicating an independent regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
121
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 35 publications
6
121
0
1
Order By: Relevance
“…Our observation, that the elastin peptide-induced signaling pathway includes activation of G protein and consecutive phosphorylation of 60-kDa c-Src, seems to be consistent with the report of Nebigil and colleagues (73) who demonstrated that c-Src plays an upstream role in the trans-activation of the PDGF receptor in the mitogenic signaling propagated by the G protein-coupled receptor interacting with 5-hydroxytryptamine. The possibility of the interaction vice versa was excluded by the fact that inactivation of PDGF receptor kinase by AG1295 did not diminish phosphorylation of 60-kDa c-Src induced by elastin peptides (Fig.…”
Section: Figsupporting
confidence: 93%
“…Our observation, that the elastin peptide-induced signaling pathway includes activation of G protein and consecutive phosphorylation of 60-kDa c-Src, seems to be consistent with the report of Nebigil and colleagues (73) who demonstrated that c-Src plays an upstream role in the trans-activation of the PDGF receptor in the mitogenic signaling propagated by the G protein-coupled receptor interacting with 5-hydroxytryptamine. The possibility of the interaction vice versa was excluded by the fact that inactivation of PDGF receptor kinase by AG1295 did not diminish phosphorylation of 60-kDa c-Src induced by elastin peptides (Fig.…”
Section: Figsupporting
confidence: 93%
“…Whole-mount immunohistochemical staining of embryos for developing blood vessels with antiplatelet endothelial cell adhesion molecule (PharMingen 01951D) antibody were performed as described (11). Western blot analysis for ErbB-2 and platelet-derived growth factor receptor-␤ (SC-432) was performed in the whole embryo or cell lysate as described (16).…”
Section: -Ht2bmentioning
confidence: 99%
“…Thymidine incorporation was detected in cardiomyocytes as described (16). Briefly, quiescent cells (24-h serum starved) were treated with 5-HT (1 M) or neuregulin (heregulin) (25 g͞ml) for 16 h, and 0.5 mCi of [ 3 H]thymidine was added to the culture during the last 4 h of incubation.…”
Section: -Ht2bmentioning
confidence: 99%
See 1 more Smart Citation
“…5-HT binding to either 5-HT 2 subclass activates G q protein and stimulates phospholipase C (PLC␤), thereby initiating a rapid release of inositol 1,4,5-trisphosphate (IP 3 ) and a rise in intracellular calcium level (6). The 5-HT 2B receptor is also coupled to the ras/mitogen-activated protein kinase cascade (7) and cross-talks with tyrosine kinase pathways to promote cell proliferation (8). In addition, the 5-HT 2B receptor recruits both cellular and inducible nitric-oxide (NO) synthase (NOS) transduction pathways through a type I PDZ domain (9).…”
mentioning
confidence: 99%